The Influence of Health Services Factor on the Maintenance of Leprosy Elimination Status at Community Health Centers in Timor-Leste - José Barreto; Nelson Eduardo Martins; Luis dos Reis (Riviera Publishing, 2026)
Introduction: Leprosy is a chronic disease caused by Mycobacterium leprae and manifests as damage to the skin and peripheral nerves. Globally, a total of 176,176 cases (0.2 cases per 10,000 population) were recorded for treatment at the end of 2015. Southeast Asia accounted for 72% of the global burden of new cases and 60% of global leprosy disabilities. Out of 14 countries globally reporting more than 1,000 cases annually, six are from the Southeast Asian Region. Method: This research is an epidemiological analytic study using a cross-sectional approach. The study population includes all managers and leprosy focal points from all Community Health Centers (CHCs) in Timor-Leste, with an estimated number of 136. Result: The findings of the study indicate that health policy, human resources, and drug supply influence leprosy elimination status, with the following results: 0.631 > 0.05, 0.569 > 0.05, and 0.396 > 0.05, respectively, from the perspective of CHC managers, and 0.384 > 0.05, 0.195 > 0.05, and 0.071 > 0.05 from the perspective of leprosy focal points. These results show that the hypothesis of no influence of health policy, human resources, and drug supply on the maintenance of leprosy elimination status was rejected. Conclusion: Based on the results outlined above, it can be concluded that health policy, human resources, and drug supply influence the status of leprosy elimination in Timor-Leste. Despite these results, this study also found that 53% of Community Health Centers in Timor-Leste are not properly implementing activities related to these three variables.